2016
DOI: 10.1109/jlt.2016.2518863
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Multidimensional Switching Nodes for All-Optical Data Center Networks

Abstract: Abstract-This paper reports on a novel ring-based data center architecture composed of multidimensional switching nodes. The nodes are interconnected with multicore fibers and can provide switching in three different physical, hierarchically overlaid dimensions (space, wavelength and time). The proposed architecture allows for scaling in different dimensions while at the same time providing support for connections with different granularity. The ring topology reduces the number of different physical links requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…At the access tier each ToR switch is connected to a single ROADM. Space division multiplexing (SDM) is also considered in alloptical DCN solutions, e.g., [15] [16] for improving capacity. In [15], four architectures based on SDM are proposed, and it is shown that these architectures are suitable to apply in different DCs depending on their size and work load.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…At the access tier each ToR switch is connected to a single ROADM. Space division multiplexing (SDM) is also considered in alloptical DCN solutions, e.g., [15] [16] for improving capacity. In [15], four architectures based on SDM are proposed, and it is shown that these architectures are suitable to apply in different DCs depending on their size and work load.…”
Section: Related Workmentioning
confidence: 99%
“…By replacing EPSs with optical switches, the reduced power-demanding electrical-to-optical (E/O) and optical-to-electrical (O/E) conversion is expected to dramatically decrease the power consumption of data center networks [8]. Several optical interconnect architectures for DCs are proposed in literature in recent years, e.g., [13]- [16]. These architectures employ all-optical switches based on different topologies and technologies at aggregation/core layer, but rely on conventional EPSs at ToR to interconnect servers in the racks.…”
Section: Introductionmentioning
confidence: 99%
“…However, the need for extra components, ultimately leading to higher component cost and additional control overhead has shown to be detrimental for the lack of deployment. In order to provide support for optical subwavelength switching while at the same time avoiding the need for optical buffering in the network, we have previously proposed the concept of optical TDM switching [2,3]. Comparing optical TDM switching against OPS and OBS, the main difference lays in the nature of the connections.…”
Section: A Optical Tdm Switchingmentioning
confidence: 99%
“…The main network scenario for optical subwavelength switching in this work is intra data center network, based on the architecture proposed in [2,3] where the optical TDM switches are connected in a ring. The focus is therefore on the synchronization requirements for such a network.…”
Section: Proposed Synchronization Algorithmmentioning
confidence: 99%
See 1 more Smart Citation